2015
DOI: 10.1039/c5tb00921a
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous structured carbon nanofiber–bioactive glass composites for skeletal tissue regeneration

Abstract: Bioactive glass (BG) decorated nanoporous composite carbon nanofibers (PCNF-BG) were prepared for the purpose of obtaining effective substrates for skeletal tissue regeneration. The preparation was conducted by electrospinning of polyacrylonitrile (PAN)-polymethylmethacrylate (PMMA) blends with the addition of sol-gel precursors of 58s-type (mol%: 58% SiO 2 -38% CaO-4% P 2 O 5 ) BG, followed by high temperature thermal treatment. The removal of PMMA during the carbonization of PAN generated numerous slit-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 47 publications
(88 reference statements)
0
21
0
Order By: Relevance
“…CNF-reinforced polymer scaffolds can also be fabricated by easily dispersing the CNF in a polymer matrix, followed by either melt mixing or sonication in low viscosity solutions [83]. Several studies have mentioned applications of CNFs in neural [84,85], bone [86][87][88][89], muscle [90], and cardiac regeneration [91][92][93].…”
Section: Carbon Nanofibersmentioning
confidence: 99%
“…CNF-reinforced polymer scaffolds can also be fabricated by easily dispersing the CNF in a polymer matrix, followed by either melt mixing or sonication in low viscosity solutions [83]. Several studies have mentioned applications of CNFs in neural [84,85], bone [86][87][88][89], muscle [90], and cardiac regeneration [91][92][93].…”
Section: Carbon Nanofibersmentioning
confidence: 99%
“…have been shown to have a great potential in regenerative medicine and tissue engineering, due to their ability to mimic the structural properties of native bone tissues. [10][11][12][13] The great research efforts for designing the ideal bio-nanocomposite scaffolds for repair and regeneration of damaged/diseased tissues have revealed the promise of polymer based bio-nanocomposite scaffolds, which exhibited superior biological properties for bone tissue engineering because allowed tailoring the desired bioactivity, degradation and resorption kinetics of the scaffolds. [14][15][16] Moreover, nanosized bioactive llers incorporated in the polymeric scaffolds offer the required osteoconductivity and biocompatibility features that are able to improve the cell adhesion, proliferation and differentiation, as well as, new bone tissue ingrowth into the scaffolds, and ultimately repair bone defects.…”
Section: Introductionmentioning
confidence: 99%
“…would benefit for cells/tissues ingrowth and nutrient delivery. 17,20 In this study, bioactive and degradable scaffolds of n-MS/ZN/PCL ternary composites were developed by using 3D-printing technology. The results showed that the pore morphology, pore interconnection, pore size as well as porosity of the (C0, C10 and C20) scaffolds could be controlled by using 3D-printing technique, and the highly interconnected scaffolds possessed the controllable macropores size of around 500 μm and porosity of around 70%.…”
Section: Discussionmentioning
confidence: 99%